Collaborative Governance dalam Pengelolaan Wisata Alam Green Canyon di Desa Medalsari Kecamatan Pangkalan Kabupaten Karawang - Wida Lestari; Eka Yulyana; Lina Aryani (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine and analyze collaborative governance in the management of Green Canyon Nature Tourism in Medalsari Village, Pangkalan District, Karawang Regency. In analyzing the author uses Ansel and Gash's collaborative governance theory which has four variable dimensions including initial conditions, institutional design, facilitative leadership and collaboration processes. This research is a descriptive qualitative type with data collection taken through the triangulation technique of interview, observation and documentation and then analyzed through three stages, namely reduction, presentation and conclusion drawing. The results of this study indicate that collaboration in the management of Green Canyon Nature tourism does not run optimally because of the lack of participation and knowledge of the actors involved, both public and private, and the government's role in initiating collaboration with the public and private sector is not visible.